Automatic Singlet Peak Analysis of Hpnal YsisiOf Hp (Ge) y-Ray Spectrum - Fattah, Aziz H.; Ahmed, Ali H.; Rasheed, Mariwan A. (Sulaimani Journal for Pure and Applied Sciences, 2003)
A computation program is applied for analysing of y-ray spectra which obtained with high-pure germanium, Hp(Ge), spectrometers in Erbil region. The program concerns the individual peak identification by defining the position and region of the peak that is significantly above the local spectral background. Each peak region, that is represented y a gaussian function underlying a linear backgound , is fitted by following Marquardt searching method to get the best peak parameters . By using the coded program relative intensities and energies have been calculated for each singlet peaks.
Keywords: Nuclear physics detection of nuclear radiation analysis of gamma ray spectrum